Lithium battery negative electrode material, preparation method and application thereof, and lithium metal battery

By forming metal carbon alloys and conductive layers in the negative electrode material of lithium metal battery, the problem of dendritic growth of lithium metal dendritics is solved, and the safety and cycle life of the battery are improved.

CN119890291AInactive Publication Date: 2025-04-25HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510014073.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the cycle of deposition/peeling of lithium metal on the surface of lithium metal negative electrode, dendritic dendrites form, resulting in reduced battery safety and shortened cycle life.

Method used

By providing a mixture with a molar ratio of nickel salt, zinc salt, nitrogen-containing organic matter and sugar compounds of (1-3): (1-3): (6-15): (1-3), carbonized at 700-900°C after spray drying, a metal carbon alloy and a conductive layer are formed to inhibit dendritic growth of lithium dendrites.

Benefits of technology

It realizes uniform deposition/peeling of lithium metal on the surface of the negative electrode material under high current density, inhibits dendritic growth of lithium dendrites, and improves the safety and cycle life of lithium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890291A_ABST
    Figure CN119890291A_ABST
Patent Text Reader

Abstract

The invention provides a lithium battery negative electrode material, a preparation method and application thereof, and a lithium metal battery, and relates to the technical field of lithium ion battery negative electrode materials. The preparation method of the lithium battery negative electrode material comprises the following steps: S1, providing a nickel salt, a zinc salt, a nitrogen-containing organic matter and a carbohydrate according to a molar ratio of (1-3): (1-3): (6-15): (1-3), dissolving in deionized water, and carrying out spray drying to obtain solid powder; and S2, carbonizing the solid powder in a protective atmosphere at 700-900 DEG C for 60-180 minutes to obtain black powder, namely the lithium battery negative electrode material. The lithium battery negative electrode material has excellent lithium metal affinity, dendritic crystal growth inhibition capability and carrier transport capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a negative electrode material for lithium batteries, a preparation method and application thereof, and a lithium metal battery. Background Art

[0002] With the national "carbon peak" and "carbon neutrality" goals, intermittent renewable resources such as wind, solar, hydro and geothermal energy account for an increasingly higher proportion in the energy structure, so large-scale energy storage technology has become an urgent need in today's society. Among many energy storage systems, electrochemical energy storage is widely used due to its high conversion efficiency, excellent cycle performance and environmental friendliness. Among many electrochemical energy storage systems, lithium-ion batteries stand out due to their high energy density, small size and long cycle life.

[0003] Today, commercial graphite-based negative electrode materials are limited by their theoretical specific capacity and cannot be further developed, which limits the further improvement of the energy density of commercial lithium-ion batteries. In recent years, scientists have made a lot of efforts to explore high-capacity negative electrode materials, such as sulfide, phosphide alloy negative electrodes and lithium metal negative electrodes. Among the many high-capacity negative electrode materials, lithium metal negative electrodes have an ultra-high theoretical specific capacity (3860mAh g -1 ) and the lowest standard hydrogen potential (-304Vvs(H + / H2)). Different from the insertion / extraction reaction mechanism of the traditional graphite anode, the lithium metal anode undergoes Li + / Li 0 deposition / stripping reaction.

[0004] Before the commercial application of lithium metal anodes, there are two key issues that need to be solved urgently, namely safety and cycle life. During the cyclic process of lithium metal deposition / stripping on the surface of the anode, as the number of cycles increases, the lithium metal will grow longitudinally on the surface of the anode to form branch-like metal dendrites. Sharp metal dendrites will pierce the diaphragm, causing the positive and negative electrodes to contact, causing internal short circuits in the battery, and causing safety accidents such as fire. More importantly, the generation of lithium dendrites will consume more active lithium and electrolyte, resulting in a decrease in the coulombic efficiency of the battery and a shortened cycle life. Therefore, how to inhibit the growth of lithium dendrites on the surface of the anode during the cycle of lithium metal batteries is a key issue in promoting the commercialization of lithium metal batteries. Summary of the invention

[0005] 1. Technical issues to be solved

[0006] In view of the shortcomings of the prior art, the present invention provides a lithium battery negative electrode material and a preparation method and application thereof, and a lithium metal battery, which solves the technical problem that lithium metal grows longitudinally on the surface of the lithium metal negative electrode to form branch-like metal dendrites during the cyclic process of lithium metal deposition / stripping on the surface of the lithium metal negative electrode.

[0007] (II) Technical solution

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a negative electrode material for a lithium battery, comprising the following steps:

[0010] S1. Provide nickel salt, zinc salt, nitrogen-containing organic matter, and sugar compound in a molar ratio of (1-3): (1-3): (6-15): (1-3), dissolve them in deionized water, and obtain solid powder after spray drying;

[0011] S2. Carbonizing the solid powder in a protective atmosphere at 700-900° C. for 60-180 min to obtain a black powder, which is a negative electrode material for a lithium battery.

[0012] In the above method, under the conditions of carbonization at 700-900°C, the molar ratio of nickel salt, zinc salt, nitrogen-containing organic matter and sugar compound is (1-3): (1-3): (6-15): (1-3), metal ions in situ catalyze the growth of nitrogen-containing organic matter to form a lithium battery negative electrode material with the metal carbon alloy as the center and the conductive layer in situ growing longitudinally on the metal carbon alloy, that is, under this condition, the metal carbon alloy generates a conductive layer, so that the conductive layer grows in situ on the metal carbon alloy, and the inhibitory effect of the conductive layer in situ growing on the metal carbon alloy on the dendritic growth of lithium dendrites is greatly improved compared with the inhibitory effect achieved by physically mixing the conductive layer material with the metal carbon alloy in the preparation of the metal carbon alloy. The metal carbon alloy has excellent affinity for lithium metal and can guide the uniform deposition of metal lithium on the surface of the negative electrode material of the lithium battery, thereby inhibiting the dendritic growth of lithium dendrites. The formed conductive layer has excellent electronic conductivity, which effectively reduces the impedance of the electrode material and the local current density. The metal-carbon alloy induces the formation of a conductive layer, which is grown in situ on the metal-carbon alloy, and can inhibit the dendritic growth of lithium dendrites, thereby achieving continuous and uniform deposition / stripping of lithium metal on the surface of the negative electrode material of the lithium battery under high current density, thereby inhibiting the dendritic growth of lithium dendrites.

[0013] Preferably, S1 satisfies at least one of the following conditions:

[0014] Nickel salt, zinc salt, nitrogen-containing organic matter and sugar compound are dissolved in a solvent and spray-dried to obtain solid powder, thereby making the nickel salt, zinc salt, nitrogen-containing organic matter and sugar compound mixed more uniformly.

[0015] The nickel salt is selected from at least one of nickel nitrate, nickel chloride and nickel sulfate;

[0016] The zinc salt is selected from at least one of zinc nitrate, zinc chloride and zinc sulfate;

[0017] The nitrogen-containing organic matter is selected from at least one of melamine, dicyandiamide and urea;

[0018] The organic carbohydrate is selected from at least one of glucose, sucrose and maltose.

[0019] Preferably, S2 satisfies at least one of the following conditions:

[0020] The black powder is firstly pickled and then washed to neutrality, and then dried to obtain the negative electrode material of the lithium battery; thereby removing impurities in the black powder.

[0021] The protective atmosphere is selected from nitrogen or argon.

[0022] Preferably, the preparation method satisfies at least one of the following conditions:

[0023] The acidic solution for pickling is selected from hydrochloric acid, sulfuric acid, and nitric acid, and the concentration of the acidic solution is 1 to 3 mol L -1 ;

[0024] The pickling time is 4 to 8 hours;

[0025] The drying is carried out in a vacuum drying oven at a drying temperature of 60 to 120° C. and a drying time of 20 to 40 hours.

[0026] In a second aspect, the present invention provides a lithium battery negative electrode material prepared by the preparation method described in the first aspect, comprising:

[0027] A metal carbon alloy and a conductive layer, wherein the conductive layer is in-situ grown on the metal carbon alloy.

[0028] The metal-carbon alloy of the above-mentioned negative electrode material for lithium battery has excellent affinity for lithium metal, and can guide the uniform deposition of metal lithium on the surface of the negative electrode material for lithium battery, thereby inhibiting the dendritic growth of lithium dendrites. The conductive layer has excellent electronic conductivity, effectively reducing the impedance of the electrode material and the local current density. The conductive layer is in-situ grown on the metal-carbon alloy to further inhibit the dendritic growth of lithium dendrites, thereby achieving continuous uniform deposition / stripping of lithium metal on the surface of the negative electrode material for lithium battery at high current density, inhibiting the dendritic growth of lithium dendrites.

[0029] Preferably, the metal-carbon alloy is nickel-zinc-carbon. Nickel-zinc-carbon has excellent affinity for lithium metal and can guide the uniform deposition of metal lithium on the surface of the negative electrode material of the lithium battery, thereby inhibiting the dendritic growth of lithium dendrites.

[0030] Preferably, the nickel zinc carbon is Ni3ZnC 0.7 .Ni3ZnC 0.7 It has excellent affinity for lithium metal and can guide the uniform deposition of metallic lithium on the surface of lithium battery negative electrode materials, thereby inhibiting the dendritic growth of lithium dendrites.

[0031] Preferably, the conductive layer material is selected from hollow graphite tubes and carbon nanotubes. Hollow graphite tubes and carbon nanotubes have excellent electronic conductivity and large specific surface area, which effectively reduce the impedance of the electrode material and the local current density, thereby achieving continuous and uniform deposition / stripping of lithium metal on the surface of the negative electrode material of the lithium battery under high current density, thereby inhibiting the dendritic growth of lithium dendrites.

[0032] In a third aspect, the present invention provides an application of a lithium battery negative electrode material in the preparation of a lithium metal negative electrode material, wherein lithium metal is deposited on the surface of the lithium battery negative electrode material to obtain a lithium metal negative electrode material. The lithium battery negative electrode material comprises a metal carbon alloy and a conductive layer grown in situ thereon. The metal carbon alloy has excellent affinity for lithium metal, and can guide the uniform deposition of metallic lithium on the surface of the lithium battery negative electrode material, thereby inhibiting the dendritic growth of lithium dendrites. The conductive layer has excellent electronic conductivity, effectively reduces the impedance of the electrode material, and reduces the local current density. The conductive layer is in situ grown on the metal carbon alloy to further inhibit the dendritic growth of lithium dendrites, thereby achieving continuous uniform deposition / stripping of lithium metal on the surface of the lithium battery negative electrode material at a high current density, inhibiting the dendritic growth of lithium dendrites, and thus the prepared lithium metal negative electrode material can inhibit the dendritic growth of lithium dendrites.

[0033] Preferably, lithium metal is used as the counter electrode, and the lithium metal is deposited on the surface of the negative electrode material of the lithium battery through discharge.

[0034] In a fourth aspect, the present invention provides a lithium metal battery, the lithium metal battery comprising a working electrode and a counter electrode, the active material of the working electrode comprising the lithium battery negative electrode material according to the second aspect, and the counter electrode comprising lithium metal. During long-term cycling, the coulombic efficiency of the lithium metal battery is always maintained at an average value of 99%. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1These are high-resolution scanning electron microscope images of samples prepared in Example 1 and Comparative Examples 1-3, a-Example 1, b-Comparative Example 1, c-Comparative Example 2, d-Comparative Example 3;

[0037] Figure 2 is a deposition / stripping rate curve of a battery assembled with the negative electrode material of a lithium battery in Example 1;

[0038] Figure 3 is a deposition / stripping rate curve of a battery assembled with the negative electrode material of a lithium battery in Comparative Example 1;

[0039] Figure 4 The deposition / stripping rate curve of the battery assembled with the negative electrode material of the lithium battery of Comparative Example 2;

[0040] Figure 5 The deposition / stripping rate curve of the battery assembled with the negative electrode material of the lithium battery of Comparative Example 3;

[0041] Figure 6 is the deposition / stripping rate curve of the battery of Comparative Example 4;

[0042] Figure 7 Comparison of the coulombic efficiency of batteries assembled with the lithium battery negative electrode materials of Example 1 and Comparative Examples 1-3 and the battery of Comparative Example 4. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0045] Example 1

[0046] This embodiment provides a method for preparing a negative electrode material for a lithium battery, which specifically includes the following steps:

[0047] S1. Weigh 1 mmol of nickel nitrate, 1 mmol of zinc nitrate, 9 mmol of melamine and 2 mmol of glucose respectively, dissolve them in deionized water, and spray dry them to obtain solid powders;

[0048] S2. In an argon atmosphere, the powder obtained in S1 is sintered in a quartz tube at a sintering temperature of 800° C. for 120 min to obtain a black powder;

[0049] S3, the black powder obtained in S2 was placed in 1 mol L -1 The obtained product was acid-washed in HCl solution for 6 h, then washed with deionized water until neutral, and then dried in a vacuum drying oven at 80 °C for 30 h to obtain a negative electrode material for a lithium battery.

[0050] Example 2

[0051] This embodiment provides a method for preparing a negative electrode material for a lithium battery, which specifically includes the following steps:

[0052] S1. Weigh 1 mmol of nickel nitrate, 1 mmol of zinc nitrate, 6 mmol of melamine and 1 mmol of glucose, dissolve them in deionized water, and spray dry them to obtain a solid powder;

[0053] S2. In an argon atmosphere, the powder obtained in S1 was sintered in a quartz tube at a sintering temperature of 700° C. for 180 min to obtain a black powder;

[0054] S3, the black powder obtained in S2 was placed in 2 mol L -1 The obtained product was acid-washed in HCl solution for 4 h, then washed with deionized water until neutral, and then dried in a vacuum drying oven at 80 °C for 30 h to obtain a negative electrode material for a lithium battery.

[0055] Example 3

[0056] This embodiment provides a method for preparing a negative electrode material for a lithium battery, which comprises the following steps:

[0057] S1. Weigh 1 mmol of nickel nitrate, 1 mmol of zinc nitrate, 15 mmol of melamine and 3 mmol of glucose, dissolve them in deionized water, and spray dry them to obtain a solid powder;

[0058] S2. In an argon atmosphere, the powder obtained in S1 is sintered in a quartz tube at a sintering temperature of 900° C. for 60 min to obtain a black powder;

[0059] S3, the black powder obtained in S2 was placed in 3 mol L -1 The obtained product was acid-washed in HCl solution for 8 h, then washed with deionized water until neutral, and then dried in a vacuum drying oven at 80 °C for 30 h to obtain a negative electrode material for a lithium battery.

[0060] Comparative Example 1

[0061] The difference between this comparative example and Example 1 is that melamine is not added to S1, and the other parts are the same as Example 1.

[0062] Comparative Example 2

[0063] The difference between this comparative example and Example 1 is that the molar amounts of the metal salt and the organic matter in S1 are 4 mmol of nickel nitrate, 4 mmol of zinc nitrate, 16 mmol of melamine and 4 mmol of glucose, and the rest are the same as in Example 1.

[0064] Comparative Example 3

[0065] The difference between this comparative example and Example 1 is that the carbonization temperature in S2 is 680° C., and the rest is the same as Example 1.

[0066] The lithium battery negative electrode materials of Example 1 and Comparative Examples 1-3 were observed using a high-resolution scanning electron microscope. Figure 1 .

[0067] from Figure 1 As can be seen in (a), the negative electrode material of the lithium battery in Example 1 is rich in carbon nanotubes. The carbon nanotubes are entangled with each other to form a network structure. At one end of the carbon nanotubes, there is a spherical block Ni3ZnC 0.7 , which fully proves that Ni3ZnC 0.7 @ Successful preparation of HGT composite materials. The carbon nanotubes are intertwined to form a network structure, which is conducive to the full exposure of active sites and the rapid transmission of electrons and ions, effectively reducing the impedance of the electrode material and the local current density, thereby achieving continuous and uniform deposition / stripping of lithium metal on the surface of the negative electrode material of the lithium battery at a high current density, thereby inhibiting the dendritic growth of lithium dendrites. Ni3ZnC 0.7 It has excellent affinity for lithium metal and can guide the uniform deposition of metallic lithium on the surface of lithium battery negative electrode materials, thereby inhibiting the dendritic growth of lithium dendrites.

[0068] from Figure 1 (b) It can be seen that the negative electrode material of the lithium battery in Comparative Example 1 lacks a nitrogen source and does not contain carbon nanotubes and metal-carbon alloy Ni3ZnC 0.7 The material agglomerates to form a blocky carbon structure. This structure greatly hinders the contact between lithium metal and active sites and promotes the growth of lithium dendrites. Figure 1 (c) Figure 1 As can be seen from Figure (d), the negative electrode materials of lithium batteries in Comparative Examples 2 and 3 have inappropriate ratios of metal salt to organic matter or carbonization temperature, and carbon nanotubes and metal-carbon alloy Ni3ZnC 0.7 The number of carbon nanotubes decreases sharply. Fewer carbon nanotubes cannot form a network structure, which is not conducive to the transmission of electrons and ions, and also increases the impedance of the electrode material. Under high current density, it is easy to promote the dendritic growth of lithium dendrites. Metal carbon alloy Ni3ZnC 0.7The number of carbon nanotubes is small, which can easily promote the dendritic growth of lithium dendrites. 0.7 In terms of the formation of carbon, there is a synergistic effect among nitrogen source, the ratio of metal salt to organic matter and the carbonization temperature.

[0069] The lithium battery negative electrode materials prepared in Example 1 and Comparative Examples 1-3 were assembled into button batteries, and the assembly scheme was as follows:

[0070] 80 wt% of the negative electrode material of lithium battery prepared in Example 1 and Comparative Examples 1-3, 10 wt% of conductive carbon black (SP) and 10 wt% of CMC were dissolved in a certain amount of deionized water and stirred continuously to form a uniform electrode slurry. After stirring for 12 hours, a 100 μm scraper was used to evenly coat the slurry on the surface of copper foil and vacuum dried at 100 ° C for 12 hours. The final electrode sheet had an active material loading of about 1.5 mg cm -2 The electrode sheet was used as the working electrode, lithium metal was used as the counter electrode, polypropylene (PP) was used as the separator, and the electrolyte was 1 mol L -1 LiPF6 was dissolved in ethylene glycol dimethyl ether and assembled into 2032 type button cells in a glove box under argon atmosphere. The electrochemical performance of each cell was tested under the same test conditions. The deposition / stripping rate curves of each cell are shown in Figure 2. Figure 2 to Figure 5 The constant current charge and discharge test was performed on a Neware test instrument (BTS-CT-4008).

[0071] Among them, the electrode sheet prepared from the negative electrode material of the lithium battery is used as the working electrode, and the lithium metal is used as the counter electrode. During the constant current charge and discharge test, the lithium metal is deposited on the surface of the negative electrode material of the lithium battery through discharge, thereby obtaining the lithium metal negative electrode material, that is, the prepared 2032 button battery is a lithium metal battery. Since the carbon nanotubes in the negative electrode material of the lithium metal battery are entangled with each other to form a network structure, the active sites are fully exposed, the electron and ion transmission speed is fast, the impedance of the electrode material is effectively reduced, and the local current density is reduced, so that the lithium metal can be continuously and uniformly deposited / stripped on the surface of the negative electrode material at a high current density, thereby inhibiting the dendritic growth of lithium dendrites during the charge and discharge process. And the Ni3ZnC in the negative electrode material 0.7 It has excellent affinity for lithium metal, can guide the uniform deposition of lithium metal on the surface of negative electrode materials, and further inhibit the dendritic growth of lithium dendrites. Therefore, the lithium metal battery prepared under the synergistic effect of nitrogen source, the ratio of metal salt to organic matter and carbonization temperature has excellent electrochemical performance.

[0072] Comparative Example 4

[0073] In this comparative example, copper foil was directly used as the working electrode, lithium metal was used as the counter electrode, polypropylene (PP) was used as the separator, and the electrolyte was 1 mol L -1 LiPF6 was dissolved in ethylene glycol dimethyl ether and assembled into a 2032-type button cell in an argon atmosphere in a glove box. The electrochemical performance was tested under the same test conditions. The deposition / stripping rate curve of the battery is shown in the figure. Figure 6 The constant current charge and discharge test was performed on a Neware test instrument (BTS-CT-4008).

[0074] Depend on Figure 2 It can be seen that under different current densities, during the continuous deposition / stripping process, the material of Example 1 exhibits extremely small nucleation overpotential and excellent cycle stability. This is due to the full exposure of the lithium-philic active sites of the negative electrode material, which greatly promotes the uniform deposition of lithium metal and reduces the overpotential of lithium metal nucleation, thereby inhibiting the longitudinal growth of dendritic lithium dendrites. At the same time, the abundant carbon nanotubes provide excellent electronic conductivity for the composite material, reduce the impedance of the electrode as a whole, and reduce the local current density. Therefore, even at a larger current density, the material of Example 1 still maintains good lithium metal deposition / stripping ability, which ensures the application potential of lithium metal batteries in fast charging.

[0075] Depend on Figure 3-5 It can be seen that under different current densities, during the continuous deposition / stripping process, the materials of Comparative Examples 1-3 exhibited a large nucleation overpotential and poor cycle stability. This is because the negative electrode materials for lithium batteries prepared in the absence of a nitrogen source or an inappropriate ratio of metal salt to organic matter or an inappropriate carbonization temperature do not contain carbon nanotubes and metal-carbon alloy Ni3ZnC 0.7 Carbon nanotubes and metal-carbon alloy Ni3ZnC generated or produced 0.7 The amount of Ni3ZnC metal anode materials is drastically reduced, that is, the prepared lithium metal anode materials are either aggregated to form a bulk carbon structure, or carbon nanotubes and metal carbon alloys Ni3ZnC 0.7 The number of carbon nanotubes decreases sharply, and the agglomeration into a blocky carbon structure greatly hinders the contact between lithium metal and active sites, promoting the growth of lithium dendrites. The carbon nanotubes are too few to form a network structure, which is not conducive to the transmission of electrons and ions, and increases the impedance of electrode materials. At high current density, such as 3mA cm -2 ,, easily promote the dendritic growth of lithium dendrites, metal carbon alloy Ni3ZnC 0.7 The number of them is small, which can easily promote the dendritic growth of lithium dendrites.

[0076] Depend on Figure 6It can be seen that under different current densities, during the continuous deposition / stripping process, the copper foil exhibits a large nucleation overpotential and poor cycle stability. It can be seen that the lithium battery negative electrode material of the present invention has a very low lithium metal nucleation overpotential and excellent cycle stability compared to the original current collector, and has great application value in the field of lithium metal negative electrodes.

[0077] Figure 7 The coulombic efficiency of the battery prepared by the negative electrode materials of the lithium battery of Example 1 and Comparative Examples 1-3 and the battery prepared by Comparative Example 4 represents the reversibility of the deposition / stripping of lithium metal on the negative electrode surface, which is crucial to the cycle stability of the battery. Figure 7 It is known that the first cycle coulombic efficiency of the negative electrode material of the lithium battery of Example 1 is as high as 98.5%, proving that the deposition / stripping of lithium metal on the negative electrode surface is an almost completely reversible process. In addition, during the long-term cycle process, the coulombic efficiency of the negative electrode material of the lithium battery of Example 1 always remains at an average value of 99%, fully proving the excellent lithium metal affinity, dendrite growth inhibition ability and carrier transport ability of the electrode material.

[0078] In summary, compared with the prior art, the present invention has the following beneficial effects:

[0079] The invention forms a lithium battery negative electrode material with a metal-carbon alloy as the center and a conductive layer growing longitudinally on the center through in-situ catalytic growth of nitrogen-containing organic matter by metal ions. The lithium battery negative electrode material has excellent lithium metal affinity, dendrite growth inhibition ability and carrier transmission ability.

[0080] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0081] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a negative electrode material for a lithium battery, characterized in that: The steps include: S1, providing nickel salt, zinc salt, nitrogen-containing organic matter, and sugar compound in a molar ratio of 1-3:1-3:6-15:1-3, dissolving them in deionized water, and spray drying to obtain a solid powder; S2. Carbonizing the solid powder in a protective atmosphere at 700-900° C. for 60-180 min to obtain a black powder, which is a negative electrode material for a lithium battery.

2. The preparation method according to claim 1, characterized in that S1 satisfies at least one of the following conditions: Nickel salt, zinc salt, nitrogen-containing organic matter and sugar compound are dissolved in a solvent and spray-dried to obtain a solid powder; The nickel salt is selected from at least one of nickel nitrate, nickel chloride and nickel sulfate; The zinc salt is selected from at least one of zinc nitrate, zinc chloride and zinc sulfate; The nitrogen-containing organic matter includes at least one of melamine, dicyanamide and urea; The organic carbohydrate is selected from at least one of glucose, sucrose and maltose.

3. The preparation method according to claim 1, characterized in that: S2 satisfies at least one of the following conditions: The black powder is firstly acid-washed and then cleaned to neutrality, and then dried to obtain the negative electrode material of lithium battery; The protective atmosphere is selected from nitrogen or argon.

4. The preparation method according to claim 1, characterized in that: At least one of the following conditions is met: The acidic solution for pickling is selected from hydrochloric acid, sulfuric acid, and nitric acid, and the concentration of the acidic solution is 1 to 3 mol L -1 ; The pickling time is 4 to 8 hours; The drying is carried out in a vacuum drying oven at a drying temperature of 60 to 120° C. and a drying time of 20 to 40 hours.

5. A lithium battery negative electrode material prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The invention comprises a metal-carbon alloy and a conductive layer, wherein the conductive layer is in-situ grown on the metal-carbon alloy.

6. The negative electrode material for a lithium battery according to claim 5, characterized in that: The metal carbon alloy is nickel-zinc-carbon; the conductive layer material is selected from hollow graphite tubes and carbon nanotubes.

7. The negative electrode material for a lithium battery according to claim 5, characterized in that: The nickel zinc carbon is Ni3ZnC 0.7 .

8. Application of a lithium battery negative electrode material in the preparation of a lithium metal negative electrode material, characterized in that: Lithium metal is deposited on the surface of the lithium battery negative electrode material according to any one of claims 5 to 7 to obtain a lithium metal negative electrode material.

9. The use according to claim 8, characterized in that Lithium metal is used as a counter electrode and is deposited on the surface of the negative electrode material of the lithium battery through discharge.

10. A lithium metal battery, characterized in that: The lithium metal battery comprises a working electrode and a counter electrode, the active material of the working electrode comprises the lithium battery negative electrode material according to any one of claims 5 to 7, and the counter electrode comprises lithium metal.

Citation Information

Patent Citations

  • Porous carbon composite material for battery membrane and preparation method and application of material

    CN110104630A

  • Nitrogen-doped carbon nanotube coated Ni3ZnC0.7 / Ni heterogeneous nanoparticle electrocatalyst and preparation method thereof

    CN115074771A

  • Nickel-zinc alloy and nickel-zinc carbide composite electrocatalyst for hydrogen production by alkaline electrolysis of water and preparation method of nickel-zinc alloy and nickel-zinc carbide composite electrocatalyst

    CN118814213A